2014
DOI: 10.3390/polym6051618
|View full text |Cite
|
Sign up to set email alerts
|

Azetidinium Functionalized Polytetrahydrofurans: Antimicrobial Properties in Solution and Application to Prepare Non Leaching Antimicrobial Surfaces

Abstract: Abstract:In this work, we report the antimicrobial efficacy of azetidinium functionalized polytetrahydrofurans in solution and their application in the preparation of non leaching, antimicrobial surfaces. The excellent antimicrobial efficacy of these water soluble polymers both in solution and on surfaces (>99.99%-100% bacterial growth inhibition) makes them excellent candidates for solving the hygiene related problems in the medical and hospital environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…1 Data analysis from U.S. Centers for Disease Control and Prevention reported that people in millions are infected with antibiotic-resistant bacteria, and thousands of them die annually due to infections in the United States. 1 Data analysis from U.S. Centers for Disease Control and Prevention reported that people in millions are infected with antibiotic-resistant bacteria, and thousands of them die annually due to infections in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 Data analysis from U.S. Centers for Disease Control and Prevention reported that people in millions are infected with antibiotic-resistant bacteria, and thousands of them die annually due to infections in the United States. 1 Data analysis from U.S. Centers for Disease Control and Prevention reported that people in millions are infected with antibiotic-resistant bacteria, and thousands of them die annually due to infections in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…5 The global market of antimicrobial coatings (AMCs) will reach $4.5 billion and nearly 590 kt of production volume by 2020, forecasted by International Antimicrobial Council, 2015. 1,5,[7][8][9] The attention is paid on the synthesis of antimicrobial reactive polymers/coatings due to their low toxicity, long-term activity, increased antimicrobial activity, high effectiveness and selectivity, stability, and also due to eco-friendly performance. ], or antibiotics); (2) contact active immobilized molecules (e.g., quaternary ammonium/chitosan polymers or peptides); or (3) light-activated molecules (e.g., TiO 2 or photosensitizers).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations